2011
DOI: 10.5770/cgj.v14i1.3
|View full text |Cite
|
Sign up to set email alerts
|

An Optometrist-Led Eye Care Program for Older Residents of Retirement Homes and Long-Term Care Facilities

Abstract: Background and PurposeVisual impairment among older adults residing in long-term care (LTC) facilities and retirement homes is common and can have a significant adverse impact on their quality of life. Despite the burden of illness, they frequently receive inadequate eye care. We describe an optometrist-led eye care program serving this population, including a profile of participants and the program’s educational role for optometry students.MethodsAn optometrist assessed residents of LTC facilities and retirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…These results consolidate the findings from previous research, in which nurses have reported feeling inadequately trained to care for residents with sensory impairment [ 43 ], and frontline healthcare providers reported difficulties in distinguishing the relative contributions of sensory loss and dementia to breakdowns in communication [ 44 , 45 ]. Despite the evidenced sensitivity and appropriateness of some sensory screening measures in older and non-communicative populations [ 27 , 46 – 49 ], as well as the feasibility of in-service training for healthcare providers who are willing to engage in these [ 16 ], and its benefit to residents with cognitive and physical fragility [ 50 ], relevant evidence-based practice guidelines have not yet been adopted in these LTCH settings [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results consolidate the findings from previous research, in which nurses have reported feeling inadequately trained to care for residents with sensory impairment [ 43 ], and frontline healthcare providers reported difficulties in distinguishing the relative contributions of sensory loss and dementia to breakdowns in communication [ 44 , 45 ]. Despite the evidenced sensitivity and appropriateness of some sensory screening measures in older and non-communicative populations [ 27 , 46 – 49 ], as well as the feasibility of in-service training for healthcare providers who are willing to engage in these [ 16 ], and its benefit to residents with cognitive and physical fragility [ 50 ], relevant evidence-based practice guidelines have not yet been adopted in these LTCH settings [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research of sensory screening measures in care settings, such as nursing homes [ 9 ], retirement homes [ 15 ], and LTCHs [ 16 ], has evidenced the need for assessment and intervention for this vulnerable population. In Canada and the United States, as in many countries across Europe and Australasia, the current standard for screening residents in these settings involves the Resident Assessment Instrument – Minimum Data Set 2.0 (RAI-MDS 2.0) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…(12) In addition, two recent clinical studies reported a high prevalence of visual deficits in older LTCF residents, (13,14) including a large proportion of individuals with cognitive deficits and communication disorders. (13) …”
Section: Introductionmentioning
confidence: 99%
“…The second part of this review has shown that there is a high prevalence of VI in LTCF/NH residents and that several factors encountered in this geriatric population, such as cognitive impairment, confusion, or poor cooperation, may render the visual examination more challenging . Nevertheless, it has also been demonstrated that it is possible to assess oculo‐visual function in LTCF/NH residents independent of their age, cognitive status or degree of communication, and that such services are very beneficial for residents, staff and family and can be offered on a regular basis . Importantly, it has been shown that residents not having any prescription glasses were often affected by VI or legal blindness, and that a simple change of prescription eyeglasses could improve the VA, decrease very significantly the amount of VI and even change a VI to a no VI in many .…”
Section: Discussionmentioning
confidence: 99%
“…The second part of this review has shown that there is a high prevalence of VI in LTCF/NH residents and that several factors encountered in this geriatric population, such as cognitive impairment, confusion, or poor cooperation, may render the visual examination more challenging . Nevertheless, it has also been demonstrated that it is possible to assess oculo‐visual function in LTCF/NH residents independent of their age, cognitive status or degree of communication, and that such services are very beneficial for residents, staff and family and can be offered on a regular basis .…”
Section: Discussionmentioning
confidence: 99%